INDONESIAN GINGER YIELD QUALITY AS THE BASIS FOR SALEABILITY OF GINGER OIL ON THE INTERNATIONAL MARKET - Wahyu Susihono (Pusbindiklat - LIPI, 2011)
Ginger Rhizome is potential to be sold in form of ginger oil. The distillation process was needed to fi nd out the most profi table ginger to be sold in form of ginger oil. The research objectives are to fi nd out comparison of “rendemen” from rind and fl esh of gajah, emprit, and red ginger using water and steam distillation process with capacity: 5000 gram of raw materials. Characteristic test performed to fi nd out the feasibility of sales accordance with Essential Oil Association Standard. Result showed that the highest rendemen is red ginger rind: 1,102%, while the lowest is gajah ginger fl esh: 0,248%. Gajah ginger oil is not feasible to be sold in world market because of it soaping number that reached 25.52%.